Dampak Kebijakan Bea Ekspor Terhadap Komoditas Kakao Kabupaten Padang Pariaman - Tanjung, Yulia Windi; Fuqara, Fantashir Awwal; Yuhendra, Alfis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyze the impact of Bea Export Policy on cocoa commodity in Padang Pariaman Regency. This study uses a quantitative survey method using questionnaires and interviews. The sampling method is proporsionate purposive sampling with 40respondence. Methods data is analyzed using Policy Analysis Matrix (PAM) and sensitivity analysis. The results showed that The Impact of government policy that is Output Policy (TO = Rp. -70.673.522,51, NPCO = 0,69), Input Policy (TI = Rp. -585.152,91, NPCI = 0,92, TF = Rp. 2480.279,36), and Input-Output Policy (EPC = 0,68, TB = Rp. -72.568.648,96, KK = -1.03, RSP = -0.97).